Study on the poroelastic behaviors of the defected articular cartilage. Issue 11 (15th August 2022) - Sun, Yuqin; Wang, Ningning; Yu, Jianhao; Yan, Yang; Dong, Hao; Wu, Xiaogang; Zhang, Meizhen; Wang, Yanqin; Li, Pengcui; Wei, Xiaochun; Chen, Weiyi
Abstract: This article presented the possible mechanism of arthritis damaged changes in cartilage's interstitial fluid flowing behavior. Firstly, the analytical solutions for the pore fluid pressure and velocity in the idealized cartilage defect model were obtained, which are employed to validate the finite element (FE) method. Then according to the MRI data, an articular cartilage FE model was developed to study the effects of defect characteristics on its poroelastic behaviors. The results showed the interstitial fluid pressure and velocity in defected articular cartilage is diminished, moreover, this trend is even more severe as the defect radius or thickness increased. As the development of osteoarthritis goes, the fluid velocity is decreased and cause the even serious nutrients loss.